(untitled) (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study examines the representation of the ideology of power in disaster management in the Japanese drama Japan Sinks: People of Hope using Teun A. van Dijk’s Critical Discourse Analysis framework. The study focuses on three analytical dimensions: text structure, social cognition, and social context. This qualitative descriptive research uses dialogues from all eight episodes of the drama as the data source. Data were collected through observation and note-taking techniques and analyzed using Van Dijk’s threedimensional model. The findings show that the ideology of power is represented through textual structures that consistently position the government as the primary authority in managing disaster situations. At the level of social cognition, the government, scientists, media, and the public construct different mental models, knowledge, attitudes, and ideologies toward disaster management. At the level of social context, the interaction among these social groups demonstrates that disaster management functions not only as a response to natural hazards but also as a discursive arena where political legitimacy, information control, and public perception are negotiated. This study contributes to Critical Discourse Analysis by explaining how audiovisual discourse reproduces the ideology of power in contemporary Japanese disaster narratives.